Mapping global inequities in telemedicine implementation: An umbrella review of barriers and facilitators - Angelo Capodici; Alessandro Filippeschi; Francesca Noci; Alessandra Michelucci; Safae El Motarajji; Vera Benedetto; Andrea Vandelli; Claudio Passino; Michele Emdin; Sabina Nuti; Carlo Alberto Avizzano; Nicola Bellè; et al. (PLoS ONE, 2026)
Telemedicine expanded rapidly during the COVID-19 pandemic, yet its diffusion has remained uneven across health systems. Whether implementation challenges differ systematically across economic contexts, and what implications these differences hold for global digital health equity, has not been comprehensively characterized. This study presents an umbrella review (PROSPERO CRD42024615998) of systematic reviews and meta-analyses indexed in PubMed and Scopus through December 2025 that reported barriers and/or facilitators to telemedicine implementation. Methodological quality was appraised using R-AMSTAR. Reported items were extracted verbatim, embedded with the Universal Sentence Encoder, and grouped into thematic clusters using HDBSCAN density-based clustering, with parameters optimized by SLSQP for cluster cohesion (median intra-cluster similarity ≥ 0.5). Analyses were stratified by World Bank country income group to characterize context-specific implementation profiles, identify evidence gaps, and detect orphaned barriers, defined as challenges lacking any corresponding documented facilitator. A total of 161 systematic reviews were included, yielding 1,333 barriers and 504 facilitators (corresponding to a barrier-to-facilitator ratio of 2.6:1). Across all settings, the most frequently reported barriers were high costs (n = 106), technical issues (n = 94), and training and knowledge (n = 91). Thematic profiles differed markedly by income group: high-income countries reported predominantly second-generation challenges centered on workflow integration, interoperability, and user experience, whereas lower-middle-income countries reported foundational barriers centered on infrastructures and costs. Evidence produced from low-income countries was entirely absent. Several high-frequency barriers lacked corresponding facilitator clusters, indicating challenges for which the published literature provides no documented solutions. The global telemedicine evidence base is itself inequitably distributed and risks reinforcing the disparities it is intended to reduce. High-income settings require implementation research focused on human and organizational factors, whereas lower-income settings require foundational research and investment in basic infrastructures before workflow-level optimization becomes meaningful. Without context-specific, equity-oriented strategies, telemedicine risks widening rather than narrowing the global digital health divide.